Geomorphometric analysis of the natural and anthropogenic seascape of Naples (Italy): A high‐resolution morpho‐bathymetric survey. Issue 5 (22nd August 2021) - Caporizzo, Claudia; Aucelli, Pietro P. C.; Di Martino, Gabriella; Mattei, Gaia; Tonielli, Renato; Pappone, Gerardo
Abstract: This research aims to reconstruct the submerged morphologies of the high‐coast sectors of Naples discriminating between landforms and anthropogenic structures, by analysing the high‐resolution data of a multibeam survey in a GIS environment. In the case of natural landforms, a signal analysis was performed to characterize the seabed and discern between sandy and rocky bottom, together with a slope analysis pointing to the detection and mapping of different orders of palaeo‐shore platforms at different bathymetric ranges and interpreted as erosional traces of the Holocene sea cliff retreat affecting the study area, mainly caused by a subsiding trend that exacerbated the glacio‐hydro‐isostatic sea‐level rise. Then, the detected palaeo‐shore platforms were further analysed to quantify their roughness degree and, consequently, the differential erosion affecting the rocky platforms. On the other hand, regarding the submerged anthropogenic structures, the multibeam survey allowed several underwater archaeological remains of Roman Age to be mapped, demonstrating the high cultural relevance of the study area.